Veterinary Practitioners' Standpoints and Comprehension towards Antimicrobial Use-Are There Opportunities for Antimicrobial Stewardship Improvement? - Zorana Kovačević; Jovana Vidović; Mihajlo Erdeljan; Marko Cincović; Zoran Ružić; Ivan Galić; Tijana Kukurić; Nenad Stojanac; Olga Horvat (MDPI AG, 2022)
The main subject of the research is the assessment of the knowledge, attitudes and behaviors of veterinarians regarding the use of antibiotics (AMU) and antimicrobial resistance (AMR) through a questionnaire conducted among veterinarians in the northern region of Serbia. A total of 62 respondents completed the questionnaire, which represents a response rate of 44.3%. Male veterinarians are less likely to be in the group of veterinarians with insufficient knowledge (p < 0.05). Veterinarians engaged in mixed practice (small and large animals) (p < 0.001) and veterinarians who have over 100 patients per month (p < 0.005) are also less likely to be in the group with insufficient knowledge of antimicrobial resistance. The proportion of those with insufficient knowledge is growing among veterinarians whose source is the Internet (p < 0.01), while the proportion of those with insufficient knowledge about antimicrobial resistance is declining among veterinarians whose source of information is continuous education (p < 0.05). The majority of the respondents (n = 59, 95.2%) completely agreed that AMR is a very big issue in the global health sector right now. Unfortunately, there are crucial gaps in the knowledge and attitudes of the surveyed participants. They do not appear to be aware of the importance of AMU in veterinary medicine and its influence on overall AMR, or the crucial part that non-prescribed antibiotics have in all of it. Positively, many veterinarians use good practice AMU guidelines in their everyday practice and in line with the global trend of AMU reduction, respondents have also decreased their AMU compared to the previous year.